Religiosidade e espiritualidade relacionadas às variáveis sociodemográficas e econonômicas e de saúde entre idosos da comunidade - SILVA, Ana Teresa de Melo e (2015)
Brazil has experienced an accelerated process of population aging, which is a global reality. Faced with the progressive aging Brazilian population context, it is necessary to know how people deal with their processes of aging and how to face them. In this way, religiosity and spirituality (R/S) occupy a prominent place in the lives of older people, because aging brings with existential questions that religion tries to answer. This study aimed to characterize the sociodemographic, economic and health of the community elders variables and determine the influence of these variables on the measures of R/S. It is a household, analytical and cross-sectional survey carried out with 643 elderly in the city of Uberaba-MG. The instruments used were: Mini Mental State Examination (MMSE), structured instrument to characterize the socio-demographic, economic and clinical indicators, Brief Multidimensional Measure of Religiousness/Spirituality (BMMRS). Data collection was held at the home of the elderly over the period from January to April 2014. The data were submitted to univariate analysis, measures of central tendency and variability, the bivariate analysis, in relation to the scores of R/S, between groups defined by categorical variables included the t-student test. For ordinal variables, under these scores included in the bivariate analysis, the Spearman correlation coefficient. On the other hand the influence of quantitative variables under these scores, used in the bivariate analysis, the Pearson correlation coefficient. Correlations were classified as fraction (0 <│r│ <0,3), moderate (0,3 ≤│r │ <0,5), strong (0,5 ≤│r │ ≤ 1,0). To analyze the predictors in the R / S, we used the multiple linear regression model, through Statistical Package for Social Sciences (SPSS), version 17.0. The level of significance of this study was α = 0,05. The project was approved by the Research Ethics Committee of UFTM, No. 493.211. Among the characteristics of the elderly, predominantly female (67,0%), with 60├69 years (42,3%), married (the) (42,1%), with 1├4 years of education (51,0%) and 1 minimum wage income (45,1%). Referring to satisfy the basic needs, 43.4% reported that meet on a regular basis, 39,8% rated their health as regular perception, 81,5% reported having two or more diseases. It was observed that the variables sex, marital status, age, education, number of diseases and health perception showed statistically significant differences in relation to the dimensions of R/S. However, no statistically significant differences between the equity and areas of R/S. Although there are few global research involving health and R/S exclusively in elderly populations. And the results of this research allowed to expand the knowledge of the socio-demographic characteristics, economic and health of older people relative to the size of R/S.